Post-fire behaviour of high-strength quenched and tempered steel under various heating conditions. (January 2020) - Wang, Xing-Qiang; Tao, Zhong; Hassan, Md Kamrul
Abstract: Quenching and tempering (QT) are common procedures in manufacturing high strength steel for building applications to achieve structural, economic and architectural benefits. However, the tempered martensitic microstructure of QT steel can change dramatically when exposing to high temperatures, leading to significant deterioration in mechanical properties. This paper investigates the post-fire mechanical properties of two types of QT steel with nominal yield stresses of 690 MPa and 1070 MPa, respectively. The main test variables include the exposure temperature (100–1200 °C), heat soak time (0.5–4 h), and cooling method (cooled in furnace, air or water). It is found that the heat soak time has obvious influence on the residual mechanical properties of QT steel, when the exposure temperature is above 500 °C. The cooling method, however, only severely affects the residual properties at a temperature above the phase change temperature (around 724 °C). It is also found that QT steel with a higher yield stress experiences more severe strength deterioration after exposure to a temperature of over 300 °C. When the exposure temperature is higher than 500 °C, however, the residual properties of the two types of steel become similar. Based on the test data in this paper and the literature, empirical equations are proposed to predict the residual elastic modulus, yield stress, ultimate strength, and ultimate strain of QT steel after exposure to elevated temperatures. Highlights: Heat soak time affects residual mechanical properties at 500 °C or above. Cooling method affects residual properties at a temperature above 700 °C. Empirical equations are proposed to predict residual mechanical properties.